2002
DOI: 10.1023/a:1013193013142
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Sodium molybdate was administered orally to adult male rat at dose level of 10, 30, and 50 mg kg body weight (5 days per week) for 60 days. At higher dose levels significant decrease in absolute and organ-to-body weight ratios of testes, epididymides, seminal vesicles and ventral prostate was observed. The sperm abnormality, associated with decrease in sperm motility and sperm count was also observed. Significant alterations in the activities of marker testicular enzymes, viz. sorbitol dehydrogenase (decreases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…Acute human Mo poisoning has also been documented in a male in his late-30s who experienced low testosterone, low libido, and psychosis among other health ailments following excessive consumption of Mo dietary supplements for an 18-day period (cumulative dose=13.5 mg, equivalent to 300-800 μg/day) (37). The evidence in humans is supported by several animal studies describing reduced testosterone, lack of libido, seminiferous tubule degeneration, reduced semen volume and sperm concentration, and poor sperm motility and morphology following the oral administration of Mo (38-43). The biological mechanism explaining the inverse association between Mo and testosterone in humans remains unclear.…”
Section: Discussionmentioning
confidence: 90%
“…Acute human Mo poisoning has also been documented in a male in his late-30s who experienced low testosterone, low libido, and psychosis among other health ailments following excessive consumption of Mo dietary supplements for an 18-day period (cumulative dose=13.5 mg, equivalent to 300-800 μg/day) (37). The evidence in humans is supported by several animal studies describing reduced testosterone, lack of libido, seminiferous tubule degeneration, reduced semen volume and sperm concentration, and poor sperm motility and morphology following the oral administration of Mo (38-43). The biological mechanism explaining the inverse association between Mo and testosterone in humans remains unclear.…”
Section: Discussionmentioning
confidence: 90%
“…Human exposure may be elevated in areas involved in the mining of Mo ore, or can also result from certain industrial operations (CDC 2005). Mo is used in the manufacture of electronic parts, glass, ceramics, and lubricants; in the production of catalysts and pigments; in steel alloys; and in chemical reagents found in hospital laboratories (CDC 2005; Pandey and Singh 2002). …”
Section: Discussionmentioning
confidence: 99%
“…In a recent study of catfish from polluted waters in the Vietnamese Mekong Delta area, Yamaguchi et al (2007) found significant inverse associations between tissue Mo, Pb, and As concentrations and gonadosomatic index (gonad weight/body weight × 100). Pandey and Singh (2002) reported a degeneration of testicular morphology and function and dose-dependent declines in sperm concentration, motility, and normal morphology in a study of rats after oral administration of sodium molybdate. The authors also reported evidence of male-mediated embryotoxicity (e.g., reduced implantation, increased pre- and postimplantation losses, and reduced fetal growth) associated with sodium molybdate exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Cadmium (Cd) can accumulate in organs and impair renal function [ 10 ]; Lead (Pb) is associated with adverse effects on the nervous, developmental, renal and reproductive systems [ 11 ]. Selenium (Se) toxicosis can cause neurological and gastrointestinal problems [ 12 ] and endocrine function disruption [ 13 ] and is a teratogen in several species of animals [ 14 ]; Molybdenum (Mo) has been shown to be a male reproductive toxicant in animals and humans [ 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%